Migration and Globalization of Chinese Christianity: Local and Transnational Dynamics in Chinese Christian Churches in Barcelona - Lamas-Abraira, Laura (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2023)
This article engages in an introductory exploration of Chinese Christianity in Spain, through a case study focused on the metropolitan area of Barcelona. The phenomenon of Chinese Christianity is contextualized through a perspective that incorporates both the local and transnational spheres, as well as an understanding of religious practice as a social fact. Based on qualitative research, this article documents the origins and organizational logics of the Chinese Christian churches in the area, as well as their social dynamics and current challenges. Finally, the importance of the migratory context both in terms of individual experience and the religious community is underlined.